Existing Problems in Getting Water Without Dam and Their Solutions - Jamolov F.N; Jurayeva N (Genius Journals, 2023)
This article presents the existing problems of large damless water intake facilities located in the middle part of the Amudarya, and their causes
Keywords: Amudarya; water intake without dams; turbidity; washing